Dampak Rekrutmen Yang Efektif, Program Orientasi dan Motivasi Karyawan Terhadap Kinerja Karyawan PT. Sunwoo Garment Indonesia - Sumi Rahmini; Agus Triatmono; M. Sukamdiani (ITB AAS Indonesia Surakarta, 2025)
This study aims to determine the impact of effective recruitment, employee orientation and motivation programs on employee performance at PT. Sunwoo Garment Indonesia. This study covers the field of marketing management. The population in this study were employees of PT. Sunwoo Garment Indonesia totaling 800 employees. The sample studied was 80 employees specifically in the production department. This sampling was done by random sampling according to the number of samples determined. The data analysis method used SPSS. Keywords : effective recruitment, employee orientation and motivation program, employee performance